Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-246x.2011.05150.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric structure beneath the Zagros collision zone resolved by non-linear teleseismic tomography

Abstract: S U M M A R YThe upper-mantle structure across the Zagros collision zone, in southwest Iran, is investigated using a non-linear weighted damped least-squares teleseismic tomography approach. The resolution of the structures/transitions in the upper mantle is enhanced significantly by correcting the teleseismic relative arrival time residuals for an a priori crustal velocity model and then performing the inversion with fixed crustal blocks. To investigate whether or not the lithospheric blocks and major transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
(75 reference statements)
9
21
1
Order By: Relevance
“…However, this thickness can not be considered as a reliable factor to control the high elevations of Zagros, which are also not underlain by the thickest crust (~ 50 km). We suggest in good agreement with Shomali et al (2011) that the high elevation in the ZFTB is supported by hot and shallow asthenosphere rather than a thickened crust and lithosphere. The same scenario was previously reported beneath the high Alborz mountain (Sodoudi et al, 2009).…”
Section: Observationssupporting
confidence: 87%
See 3 more Smart Citations
“…However, this thickness can not be considered as a reliable factor to control the high elevations of Zagros, which are also not underlain by the thickest crust (~ 50 km). We suggest in good agreement with Shomali et al (2011) that the high elevation in the ZFTB is supported by hot and shallow asthenosphere rather than a thickened crust and lithosphere. The same scenario was previously reported beneath the high Alborz mountain (Sodoudi et al, 2009).…”
Section: Observationssupporting
confidence: 87%
“…High resolution tomography images provided by Shomali et al (2011) revealed a thick continental lithosphere (more than 200 km) beneath the Arabian shield (ZFTB) and no (or very thin) lithospheric mantle under the Central Iran. Furthermore, they indicated that the low-velocity anomaly beneath UDMA continues with less intensity underneath the ZFTB to depths of about 200 km.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tomographic cross-sections presented by Alinaghi et al (2007) show northward-dipping high-velocity mantle anomalies beneath Central Iran, which can be interpreted as remnants of the subducted Neotethys oceanic lithosphere, as was later noted by Paul et al (2010). Shomali et al (2011) investigated the upper-mantle structure of the Zagros Mountains in southwest Iran, using traveltime teleseismic tomography. The results show a thick (more than 200 km) continental lithosphere in the Arabian Platform, while very thin (or no) lithospheric mantle is seen in Central Iran.…”
Section: Introductionmentioning
confidence: 82%